Clinical applications of single photon emission tomography in neuromedicine - Bartenstein, P.; Grünwald, F.; Kuwert, T.; Tatsch, K.; Sabri, O.; Benkert, O.; Fahlbusch, R.; Gründer, G.; Herzholz, K.; Weiller, C. (Nuklearmedizin - NuclearMedicine, 2000)
Single photon emission tomography is, because of its availability and the relatively low costs, the functional imaging modality currently most widely used for clinical applications in the brain. Beside the application of radiopharmaceuticals for the assessment of regional cerebral blood flow there is an increasing clinical use of more selective SPECT-radiopharmaceuticals, like amino acid analogs or receptor ligands. This article gives in his first part a critical review of the clinical applications of SPECT in neuro-oncology, epilepsy, basal ganglia disorders and cerebrovascular disease.
Keywords: Single photon emission tomography (SPECT); brain tumor; epilepsy; basal ganglia; cerebrovascular